Private Information, Earnings Manipulations, and Executive Stock-Option Exercises - Bartov, Eli; Mohanram, Partha (The Accounting Review, 2004)
This paper investigates the decision by top-level executives of more than 1,200 public corporations to exercise a large number of stock option awards in the period 1992–2001. We hypothesize and find that abnormally large option exercises predict stock return future performance. We then hypothesize that this predictive ability represents private information about disappointing earnings in the post-exercise period. Consistent with this hypothesis we find that abnormally positive earnings performance in the pre-exercise period turns to disappointing earnings performance in the post-exercise period, and that this pattern comes as a surprise to even sophisticated market participants (financial analysts). We also hypothesize and find that the disappointing earnings in the post-exercise period represent a reversal of inflated earnings in the pre-exercise period. Collectively, these findings suggest that the private information used by top-level executives to time abnormally large exercises follows from earnings management so as to increase the cash payout of exercises.